2019
DOI: 10.1108/jkm-04-2019-0204
|View full text |Cite
|
Sign up to set email alerts
|

Are there any antecedents of top-down knowledge hiding in firms? Evidence from the United Arab Emirates

Abstract: Purpose The purpose of this paper is to explore the antecedents of top-down knowledge hiding in buying and supplying firms. Design/methodology/approach This study uses a multiple case study methodology by considering four UAE-based firms and further employing 20 semi-structured interviews with managers of buying and supplying firms having a local and foreign nationality. Findings Based on the qualitative interviews, senior managers were found to be intentionally hiding knowledge from their managers based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
129
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 39 publications
(62 reference statements)
4
129
0
Order By: Relevance
“…Few studies inspect the determinants and effects of knowledge hiding within the context of the supply chain domain. For instance, Butt and Ahmad (2019) conducted a study on the antecedents of top‐down knowledge in buying and supplying firms connected in a supply chain. They further developed a model depicting antecedents at three levels including individual, interpersonal, and firm level and argued that knowledge hiding can leave supplying firms in isolation and complete vulnerability.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies inspect the determinants and effects of knowledge hiding within the context of the supply chain domain. For instance, Butt and Ahmad (2019) conducted a study on the antecedents of top‐down knowledge in buying and supplying firms connected in a supply chain. They further developed a model depicting antecedents at three levels including individual, interpersonal, and firm level and argued that knowledge hiding can leave supplying firms in isolation and complete vulnerability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although supply chain management scholars have explored the role of knowledge hiding in the supply chain management literature in past few years (Samuel et al 2011; Salazar, 2017; Rasheed et al, 2010; Butt and Ahmad, 2019; Butt, 2019), they have ignored that knowledge hiding can adversely affect the business relationship between them. Upon pursuing this goal, the goal of this pilot study was to explore how knowledge hiding might affect a business relationship between managers of buying and supplying firms in the supply chain.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current research on the phenomenon of knowledge hiding on the one hand, mainly focused on the individual knowledge hiding micro-level discussion, but knowledge hiding not only between employees, several studies show that like employees produce emotional attachment to the organization, they may give their attention on the focus of the organization, such as leader (Becker, 1992;Clugston, Howell, & Dorfman, 2000;Gregersen, 1993;Stinglhamber, Bentein, & Vandenberghe, 2002), leadership and subordinate's interaction are also the important channel which the flow of information and knowledge hiding of management is widespread (Černe et al, 2014;Connelly & Zweig, 2015;Connelly et al, 2012;Peng, 2013), Therefore, the double-effect mechanism of knowledge hiding between leaders and ordinary employees needs further exploration and analysis (Arain, Bhatti, Ashraf, & Fang, 2018;Butt & Ahmad, 2019;Fong & Slotta, 2018). On the other hand, there's a lot of research on antecedent variables of knowledge hiding, previous research has shown that employees between knowledge hidden hazards, such as creative destruction (Černe et al, 2014; Černe et al, 2017), inhibit the spread of new knowledge and development (Černe et al, 2014), and increase turnover intention (Connelly et al, 2012), etc.…”
Section: Introductionmentioning
confidence: 99%